Modeling the Non-linear Relationship between the International Prices of Oil and Wheat and the Exchange Rate in Egypt - Helmy, Heba Ezzeldin (Ekonomika, 2025)
The Egyptian pound (LE) has experienced multiple devaluations over the last few years. One of the proclaimed causes was the severe rise in the prices of Egypt’s two main imports – wheat and oil – that followed the eruption of the Russian-Ukraine war and inflated Egypt’s import bill, resulting in an increased shortage of the US dollars and creating downward pressures on the LE. Using a nonlinear autoregressive distributed lag (NARDL) method we probe whether an asymmetric relationship exists between Egypt’s exchange rate and each of the international prices of oil and wheat. Short-run asymmetric effects of oil and wheat prices on Egypt’s currency rate were found, as the latter rose in response to upsurges in the oil price and fell in response to downturns in the price of wheat, with no impacts from the opposite changes in the short run. Oil price rises may thus temporarily function as a weak hedge for the LE.
Keywords: Exchange rate; Oil price; Wheat price; ARDL; NARDL; Egypt